ANALISIS PENGARUH KOMITE AUDIT TERHADAP HUBUNGAN ANTARA ROTASI AUDITOR DAN AUDIT TENURE DENGAN KONSERVATISME AKUNTANSI - Naila Rusyda Munif; Tarmizi Achmad (Diponegoro Journal of Accounting, 2013)
The purpose of this study is to examine the impact of audit committee on auditor independence in its relation with the conservative of financial statement. The effective performance of audit committee being predicted to strengthen the positive effect of auditor rotation on accounting conservatism. Alternatively, the effective performance of audit committee has been advocated to weaken the negative effect of audit tenure on accounting conservatism. This study using financial statements and annual reports of manufacturing companies that were listed in Indonesia Stock Exchange (BEI) during 2007-2011 reporting periods. Data analysis tool used is moderated regression analysis.  The result of the study indicates that all of the main variables, that is auditor rotation, audit tenure, the effect of competence and frequency meeting of audit committee on auditor rotation, also the effect of competence and frequency meeting of audit committee on audit tenure do not significantly affect accounting conservatism.